Jaafar Taib: A biography of Malaysia versatile cartoonist / Fatimatuzzaharah Mohd Kidin and Muliyadi Mahamood (Prof. Dr.) - Mohd Kidin, Fatimatuzzaharah; Mahamood, Muliyadi (Prof. Dr.) (Universiti Teknologi MARA, 2016)
There are several successful cartoonists in Malaysia and so far the thriving life of Jaafar Taib has not been thoroughly researched and documented. The biography done so far was very brief and only discusses on his works as a cartoonist. Lack of resources on cartoon history itself has made this research crucial because cartoon has become a part of history in Malaysia. It is to enrich the documentation of cartoon art in Malaysia by focusing on the success story of a versatile cartoonist, comic artist, painter and entrepreneur Jaafar Taib. Consideration on the description, analysis, interpretation and judgment in the analysis of his art works as compared to his life journey as a versatile cartoonist are presented in three major eras, namely the formative years, productive years and the new millennium. From these three parts, his artworks will be further dissected based on the technical and aesthetic aspects as well as the literacy of it. Hence, the life of Jaafar Taib as a cartoonist, a painter and an entrepreneur for more than five decades has made him a versatile cartoonist in total. He has successfully maintained the Malaysian identity in his artwork and is considered as the best contribution towards comic industry in Malaysia by receiving awards from Prime Minister of Malaysia. It is hoped that this study will inspire others to document the success stories of other prominent local cartoonists.